2008
DOI: 10.1074/jbc.m709231200
|View full text |Cite
|
Sign up to set email alerts
|

S100A1 Binds to the Calmodulin-binding Site of Ryanodine Receptor and Modulates Skeletal Muscle Excitation-Contraction Coupling

Abstract: S100A1, a 21-kDa dimeric Ca 2؉-binding protein, is an enhancer of cardiac Ca 2؉ release and contractility and a potential therapeutic agent for the treatment of cardiomyopathy. The role of S100A1 in skeletal muscle has been less well defined. Additionally, the precise molecular mechanism underlying S100A1 modulation of sarcoplasmic reticulum Ca 2؉ release in striated muscle has not been fully elucidated. Here, utilizing a genetic approach to knock out S100A1, we demonstrate a direct physiological role of S100A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
197
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(214 citation statements)
references
References 59 publications
13
197
3
1
Order By: Relevance
“…Son homotetrámeros de alto peso molecular (~560 kDa) con un gran dominio citoplásmico y uno transmembrana que permite el funcionamiento de la proteína como un canal de Ca 2+ que regula la salida de este ión del retículo endoplásmico hacia el citoplasma (21)(22)(23)(24). Su actividad es regulada por el trifosfato de adenosina (ATP), magnesio (Mg 2+ ), Ca 2+ , el estado de oxido-reducción, el estado de fosforilación/desfosforilación y varias proteínas como la calsecuestrina, la calmodulina, la S100A1, la FKBP (FK 506 binding protein) y, posiblemente, por la proteína recién caracterizada SRP-27 (11,21,(25)(26)(27)(28)(29).…”
Section: El Mecanismo De Acoplamiento Excitación-contracción En El Múunclassified
“…Son homotetrámeros de alto peso molecular (~560 kDa) con un gran dominio citoplásmico y uno transmembrana que permite el funcionamiento de la proteína como un canal de Ca 2+ que regula la salida de este ión del retículo endoplásmico hacia el citoplasma (21)(22)(23)(24). Su actividad es regulada por el trifosfato de adenosina (ATP), magnesio (Mg 2+ ), Ca 2+ , el estado de oxido-reducción, el estado de fosforilación/desfosforilación y varias proteínas como la calsecuestrina, la calmodulina, la S100A1, la FKBP (FK 506 binding protein) y, posiblemente, por la proteína recién caracterizada SRP-27 (11,21,(25)(26)(27)(28)(29).…”
Section: El Mecanismo De Acoplamiento Excitación-contracción En El Múunclassified
“…One of the important ligands for RyR is S100A1. Prosser and colleagues used a knockout mouse (S100A1) to demonstrate that S100A1 enhances Ca 2+ release (Prosser et al, 2008). Twitch and tetanic contractile amplitudes are attenuated, and the corresponding Ca 2+ transients are smaller in the S100A1 mice compared with muscles of wildtype control mice.…”
Section: +mentioning
confidence: 99%
“…Recently, several studies demonstrated that an S100 protein, S100A1, enhances RyR1-and RyR2-dependent calcium release in both skeletal and cardiac muscle, respectively (5-10). Specifically, S100A1 knock-out skeletal muscle fibers demonstrate decreased Ca 2ϩ transients (6), and adenoviral delivery of S100A1 into failing cardiomyocytes restores myocyte contractile properties (11). Additionally, S100A1 increases [ 3 H]ryanodine binding to RyR1, indicative of increased activation of the channel (5), and S100A1 binds directly to RyR1 in a calciumdependent manner (6).…”
mentioning
confidence: 99%
“…Additionally, S100A1 increases [ 3 H]ryanodine binding to RyR1, indicative of increased activation of the channel (5), and S100A1 binds directly to RyR1 in a calciumdependent manner (6). These data suggest a possible therapeutic role of S100A1 in treatment strategies for skeletal and cardiomyopathies (6,8,11). S100A1 is a symmetric homodimer (93 residues/subunit) with each S100A1 subunit having a low affinity pseudo-EF hand and a second high affinity canonical EF hand calcium binding domain (12).…”
mentioning
confidence: 99%